ANALISIS PELUANG KEBERHASILAN PENURUNAN LAJU DEFORESTASI: PENDEKATAN TEORI TRANSISI HUTAN - Deden Djaenudin; Rina Oktaviani; Sri Hartoyo; Hariyatno Dwiprabowo (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
Indonesia is a decentralized country so that each region implements its own development policy. The economic activity imposed by the regions has implications on the diverse dynamics of forest cover, indicated by the different rates of deforestation.. This paper aims to describe the dynamics of Indonesian forest cover by using forest transition hypothesis framework and analyze the factors that accelerate the decline in deforestation rates. Refering to land cover data for period of 2000-2013 and economic variables, model of ordered logistic regression (OLR) was developed by using maximum likelihood estimation method. The result showed that, provinces in Indonesia can be classified into three groups: high, medium and low. Share of forest cover and population density increase the probability in achieving low deforestation rate. Conversely, income per capita is indicated to be a factor that inhibits the decline in deforestation rates. Acceleration of the achievement of the decrease in deforestation rates can be done through (1) enhancing the clarity of tenure, (2) improving environmental policies such as development of environmental reward system, (3) increasing value added output to improve product competitiveness; (4) conservation and reforestation, and (5) improving agricultural technology.